2009
DOI: 10.1017/s0025315409003130
|View full text |Cite
|
Sign up to set email alerts
|

Digenean trematode species in the cockle Cerastoderma edule: identification key and distribution along the north-eastern Atlantic shoreline

Abstract: We describe the digenean fauna of one of the dominant intertidal hosts, the common cockle Cerastoderma edule, in terms of biomass, off north-eastern Atlantic shores. Using published and unpublished literature we have prepared an identification key and provide an up-date of the large-scale distributional patterns of digenean species of the common cockle. At least sixteen digenean species, belonging to seven families, use cockles as intermediate host. Among these species two utilize cockles as first intermediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
75
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 71 publications
3
75
0
Order By: Relevance
“…In addition to trematode infections, cockle populations that experienced mortalities in Galicia also experienced disseminated neoplasia, which was considered to be another significant factor in contributing to the mortalities (Carballal et al 2001, Villalba et al 2001, da Silva et al 2005. Although mass mortalities were described as having occurred, these losses were not quantified, as enumerating mass mortalities in burrowing animals in their natural habitat is difficult.Of the various diseases and parasites that affect cockles, disseminated neoplasia and metazoan parasites have been reported most frequently in studies of Cerastoderma edule (Carballal et al 2001, Villalba et al 2001, Thieltges 2008, de Montaudouin et al 2009). Neoplasms in C. edule were initially recorded in 1982 in Cork Harbour, Ireland, and in that same year they were also reported in Brittany, France (Twomey & Mulcahy 1988, Twomey 1994, Villalba et al 2001, Romalde et al 2007, Le Grand et al 2010.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to trematode infections, cockle populations that experienced mortalities in Galicia also experienced disseminated neoplasia, which was considered to be another significant factor in contributing to the mortalities (Carballal et al 2001, Villalba et al 2001, da Silva et al 2005. Although mass mortalities were described as having occurred, these losses were not quantified, as enumerating mass mortalities in burrowing animals in their natural habitat is difficult.Of the various diseases and parasites that affect cockles, disseminated neoplasia and metazoan parasites have been reported most frequently in studies of Cerastoderma edule (Carballal et al 2001, Villalba et al 2001, Thieltges 2008, de Montaudouin et al 2009). Neoplasms in C. edule were initially recorded in 1982 in Cork Harbour, Ireland, and in that same year they were also reported in Brittany, France (Twomey & Mulcahy 1988, Twomey 1994, Villalba et al 2001, Romalde et al 2007, Le Grand et al 2010.…”
mentioning
confidence: 99%
“…Neoplasms in C. edule were initially recorded in 1982 in Cork Harbour, Ireland, and in that same year they were also reported in Brittany, France (Twomey & Mulcahy 1988, Twomey 1994, Villalba et al 2001, Romalde et al 2007, Le Grand et al 2010. Disseminated neoplasia is a proliferative disorder of the haemocytes and is of unknown origin; it is characterised by very large, mitotically active, pleomorphic and highly invasive cells (Twomey 1994, Krishnakumar et al 1999, Collins & Mulcahy 2003, Barber 2004, Ciocan et al 2006, Le Grand et al 2010, Díaz et al 2011.Throughout their range Cerastoderma edule are known to act as the first or second intermediate host for at least 16 digenean parasites from 7 different families, of which the family Echinostomatidae is the most dominant (de Montaudouin et al 2009). A recent study along the southwest coast of Ireland found 8 species of digenean parasites in C. edule, and Meiogymnophallus minutus (synonym Parvatrema minutus, Scholz 2002) was the most common in terms of prevalence and intensity of infection (Fermer et al 2009).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding encysted metacercariae, the wide range of cyst diameter and the variety of microhabitats within the host suggested the occurrence of larvae of the families Echinostomatidae, Renicolidae and Psilostomatidae in the Galician lagoon cockles (Lauckner 1983, de Montaudouin et al 2009, Longshaw & Malham 2013. Regarding unencysted metacercariae, both host species (C. glaucum) and anatomical location (extra-pallial space beside the mantle margin) suggested that the Gymnophallidaelike metacercariae observed in Galician lagoon cockles corresponded to Meiogymnophallus fossarum (Lauckner 1983, de Montaudouin et al 2009). High loads of metacercariae have been reported to cause damage to bivalve molluscs, including impaired growth rate, reduced capacity to burrow and increased mortality (Lauckner 1983).…”
Section: Discussionmentioning
confidence: 99%